Awareness level on Malaysia Book of Records existence among Malaysian public / Nur Cahaya Che Soo - Che Soo, Nur Cahaya (Faculty of Business Management, 2006)
The purpose of study is to identify the public awareness level on Malaysia Book of Records existence. As a non profit organization, MBR depend solely on the public to support and make sure the company can run the operation from time to time. In doing so, MBR have to study the level of public awareness, what make the public aware and how to increase the awareness level. Furthermore, the awareness level differ from one people to another, depends on the behavior that effect to their awareness. For this reason, awareness level of the public depends on how MBR choose and organize their promotional tools to get people attention and support. Therefore, if MBR serious about determining the awareness level towards their company, they should at least study a representative sample of the Malaysian Public. This paper consists of six chapters which explain the subject matter in stages. Chapter 1 explains the introduction and background of the study. Chapter 2 explains the literature review, which relates to the subject studied and chapter 3 is the theoretical framework which act as a guide to the research flow and process. For chapter 4, research methodology is explained, which consist of methods and sampling techniques being used. Data findings and discussions is explained in chapter 5, derived from the information obtain from the respondents. And finally, chapter 6 contains summary of results and findings, which explain conclusions and recommendations.